PENGARUH PRESTASI BELAJAR DAN PERSEPSI MAHASISWA TENTANG KESEJAHTERAAN GURU TERHADAP MINAT MENJADI GURU PADA MAHASISWA PRODI PENDIDIKAN AKUNTANSI FKIP UNS - -, Diyantini; Santoso, Sigit; Octoria, Dini (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThis research has purpose for knowing 1) the effect of learning achievement on the interest becoming a teacher of the students of Accounting Education Department of the FKIP UNS; 2) the effect of studentâs perception about teachers prosperity on the interest becoming a teacher of the students of Accounting Education Department of the FKIP UNS; and 3) the interaction effect of learning achievement and studentâs perception about teachers prosperity on the interest becoming a teacher of the students of Accounting Education Department of the FKIP UNS. This research uses qualitative descriptive method with ex post facto nature. The population in this research is all of the students of Accounting Education Department of the FKIP UNS period 2013 and 2014. The technique of sample interpretation that is used is purposive sampling. The technique of collecting data that is used are questionnaire and documentation. The technique of data analysis that is used are simple regression analysis, multiple regression analysis and contribution effective, meanwhile requirement test with normality test and linearity test. The result of the research the conclusions are (1) There is a positive and significant effect of learning achievement on the interest becoming a teacher of the students of Accounting Education Department of the FKIP UNS; (2) There is a positive and significant effect of students perception about teachers prosperity on the interest becoming a teacher of the students of Accounting Education Department of the FKIP UNS; and (3) There is a interaction positive and significant effect of learning achievement and students perception about teachers prosperity on the interest becoming a teacher of the students of Accounting Education Department of the FKIP UNS.Keywords: Learning Achievement, Students Perception about Teachers Prosperity, Interest Becoming a TeacherÂ ABSTRAKPenelitian ini bertujuan untuk mengetahui (1) pengaruh prestasi belajar terhadap minat menjadi guru pada mahasiswa Prodi Pendidikan Akuntansi FKIP UNS; (2) pengaruh persepsi mahasiswa tentang kesejahteraan guru terhadap minat menjadi guru pada mahasiswa Prodi Pendidikan Akuntansi FKIP UNS; dan (3) interaksi pengaruh prestasi belajar dan persepsi mahasiswa tentang kesejahteraan guru terhadap minat menjadi guru pada mahasiswa Prodi Pendidikan Akuntansi FKIP UNS. Penelitian ini menggunakan metode deskriptif kuantitatif yang bersifat ex post facto. Populasi dalam penelitian ini adalah seluruh mahasiswa Program Studi Pendidikan Akuntansi FKIP UNS angkatan 2013 dan angkatan 2014. Teknik pengambilan sampel menggunakan purposive random sampling. Teknik pengumpulan data menggunakan angket dan dokumentasi. Teknik analisis data menggunakan regresi sederhana, regresi berganda dan sumbang efektif, sedangkan uji persyaratan dengan uji normalitas dan uji linieritas menggunakan. Hasil penelitian disimpulkan: (1) Terdapat pengaruh yang positif dan signifikan prestasi belajar terhadap minat menjadi guru pada mahasiswa Prodi Pendidikan Akuntansi FKIP UNS; (2) Terdapat pengaruh yang positif dan signifikan persepsi mahasiswa tentang kesejahteraan guru terhadap minat menjadi guru pada pada mahasiswa Prodi Pendidikan Akuntansi FKIP UNS; dan (3) Terdapat interaksi pengaruh yang positif dan signifikan prestasi belajar dan persepsi mahasiswa tentang kesejahteraan guru terhadap minat menjadi guru pada mahasiswa Prodi Pendidikan Akuntansi FKIP UNS.Kata Kunci : Prestasi Belajar, Persepsi Mahasiswa tentang Kesejahteraan Guru, Minat Menjadi Guru